2023
DOI: 10.3389/fpsyg.2023.1120925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical exercise on social adaptability of college students: Chain intermediary effect of social-emotional competency and self-esteem

Abstract: ObjectiveTo explore the relationship between physical exercise and college students’ social adaptability, as well as the mediating role of social-emotional competency and self-esteem.MethodsOne thousand two hundred thirty college students were investigated by physical exercise questionnaire, social-emotional competency scale, self-esteem scale, and social adaptability scale. Data were analyzed by Pearson correlation analysis, structural equation model test and deviation-corrected percentile Bootstrap method.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…First, through empirical validation, the study confirms that physical exercise positively predicts middle school students' social adaptability, which is consistent with the findings of previous scholars, [3,18] that is, physical exercise can enhance students' ability to solve social problems and thus improve their social adaptability. Qai et al [2] also explain this through the theory of integrative adaptive development, which holds that the enhancement of adolescents' social adaptation level is based on life and learning practices, [19] and physical exercise, as a kind of challenging social practice activities, is often accompanied by a certain degree of difficulty and challenges, which requires individuals to continuously experience learning and overcome difficulties in the exercise practice, this learning and practice process of completing the challenges can undoubtedly enhance the adolescents' adaptability and ability to deal with things.…”
Section: The Effect Of Physical Exercise On Social Adaptabilitysupporting
confidence: 89%
See 1 more Smart Citation
“…First, through empirical validation, the study confirms that physical exercise positively predicts middle school students' social adaptability, which is consistent with the findings of previous scholars, [3,18] that is, physical exercise can enhance students' ability to solve social problems and thus improve their social adaptability. Qai et al [2] also explain this through the theory of integrative adaptive development, which holds that the enhancement of adolescents' social adaptation level is based on life and learning practices, [19] and physical exercise, as a kind of challenging social practice activities, is often accompanied by a certain degree of difficulty and challenges, which requires individuals to continuously experience learning and overcome difficulties in the exercise practice, this learning and practice process of completing the challenges can undoubtedly enhance the adolescents' adaptability and ability to deal with things.…”
Section: The Effect Of Physical Exercise On Social Adaptabilitysupporting
confidence: 89%
“…Although this study clarified the relationship between physical exercise, social anxiety, and social adaptability in middle school students and confirmed the mediating role of social anxiety, it did not rule out the existence of other intermediary variables. For example, Liu et al [18] confirmed the mediating role of self-esteem in the effects of physical exercise on social adaptability. The correlation between selfesteem and social anxiety has also been empirically evidenced, [32] suggesting a possible chain mediating role of self-esteem and social anxiety between physical exercise and social adaptability, and future studies can substitute self-esteem into the existing model to further enrich the pathway of physical exercise on social adaptability.…”
Section: Limitations and Future Researchmentioning
confidence: 96%